La terminologia catalana actual - Duarte, Carles (Caplletra. Revista Internacional de Filologia, 2015)
The Catalan language currently has a series of terminological resources at its disposal which award it a privileged position compared to other languages of a similar size. This situation also allows for a fitting response to new terminological requeriments arising as a result of technological development. Worthy of mention in this respect is the existence of TERMCAT, an organisation which has been a decisive factor in the promotion of terminological work. This has come about by means of the adoption of modern methodology adapted to international standards, the training of experts in terminology and the creation and publication of dictionaries. Mention should also be made of the excellent work carried out in this field by the universities and governments in Catalonia, the Community of Valencia and Andorra.